Intersections of nativism and football fandom in Zimbabwean online spaces. Issue 1 (2nd January 2023) - Ncube, Lyton
Abstract: Post-2000 Zimbabwe is characterised by the ZANU PF government's nativist nationalism. Within literature on sports in Zimbabwe, studies exploring connections between nativist nationalism and sports are scarce. This article uses the case of a 'white' Portuguese football coach, Paulo Jorge Silva, to explore intersections of nativism and football fandom in Zimbabwe's online spaces. Silva was appointed as coach of Zimbabwe's most popular Premier Soccer League team Dynamos FC in 2016. Guided by the nativism concept, selected online fandom comments targeting Silva as Dynamos FC coach, were subjected to critical discourse analysis. Comments expressed that the relationship between Dynamos and a 'white' coach was likely to end in failure since it was akin to reversing gains of the liberation struggle at a time when the government had crafted indigenous black empowerment policies.